Equality of Surgical Fee Schedule in Japan: A Retrospective Observational Study - Yoshinori Nakata; Yuichi Watanabe; Hiroshi Otake (SAGE Publishing, 2021)
The authors had previously demonstrated that the Japanese surgical fee schedule had been unequal among surgical specialties in spite of its biannual revisions. This study examined how the degree of inequality of the fee schedule changed by estimating Gini coefficients for efficiency scores computed from data envelopment analysis. All the surgeries at Teikyo University Hospital in 2013 to 2018 were candidates used for the analysis of efficiency and equality of fee schedule. Inputs were defined as (1) the number of assistants, and (2) the duration of operation. An output was defined as the surgical fee. Each surgeon's efficiency score was calculated using data envelopment analysis. Using the medians of efficiency scores in each surgical specialty, the authors inferred Gini coefficients and their standard errors in each year and in each surgical fee schedule. The authors analyzed 16 307 surgical procedures during the study period of 2013 to 2018. There was no statistically significant difference in the Gini coefficients between the years and between the surgical fee schedules ( P  > .05). It was demonstrated that the degree of inequality of the Japanese surgical fee schedule remained constant from 2013 through 2018.